2003
DOI: 10.1254/jphs.93.279
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Releasing Effect of Cerivastatin on the Sarcoplasmic Reticulum of Mouse and Rat Skeletal Muscle Fibers

Abstract: Abstract. We analyzed the effect of HMG-CoA reductase inhibitors on Ca 2+ release from the sarcoplasmic reticulum (SR) using chemically skinned skeletal muscle fibers from the mouse and the rat. Cerivastatin (>20 m M) released Ca 2+ from the SR, while pravastatin showed only a little effect. The rates of Ca 2+ release were increased by cerivastatin at all Ca 2+ concentrations tested. Cerivastatin-induced Ca 2+ release in the presence of Ca 2+ was affected by adenosine monophosphate, Mg 2+, and procaine in esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
(39 reference statements)
3
17
0
Order By: Relevance
“…Indeed, the partial and the complete lack of effect of fluvastatin observed in the presence of ruthenium red and CsA, respectively, led us to propose that a mitochondrial Ca 2ϩ efflux represents the early event, which in turn caused the subsequent large SR Ca 2ϩ release. It is noteworthy that our findings represent the first direct evidence of such mechanism on intact skeletal muscle fibers where the e-c coupling system functionality is ensured and are in agreement with previous studies performed on cultured myoblasts as well as on skinned fibers (Nakahara et al, 1994;Inoue et al, 2003;Sirvent et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the partial and the complete lack of effect of fluvastatin observed in the presence of ruthenium red and CsA, respectively, led us to propose that a mitochondrial Ca 2ϩ efflux represents the early event, which in turn caused the subsequent large SR Ca 2ϩ release. It is noteworthy that our findings represent the first direct evidence of such mechanism on intact skeletal muscle fibers where the e-c coupling system functionality is ensured and are in agreement with previous studies performed on cultured myoblasts as well as on skinned fibers (Nakahara et al, 1994;Inoue et al, 2003;Sirvent et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…After 2 to 3 months of chronic treatment of rats with simvastatin, the voltage threshold for contraction (mechanical threshold, MT), a calcium-sensitive index of excitation-contraction coupling, was shifted toward more negative potentials in fast-twitch muscle fibers (Pierno et al, 1999), an effect that is compatible with an increase of resting cytosolic calcium concentration ([Ca 2ϩ ] i ). Moreover, in vitro studies showed a statin-induced elevation of [Ca 2ϩ ] i and suggested a possible interference of the drug with intracellular Ca 2ϩ stores (Nakahara et al, 1994;Inoue et al, 2003;Sirvent et al, 2005), which in turn might be responsible of cell damages via activation of Ca 2ϩ -dependent proteolytic enzymes (Sacher et al, 2005). It is noteworthy that all statin-induced effects on skeletal muscle are strictly dependent on their lipophilicity, showing highly hydrophilic pravastatin, and no muscle toxicity, even at high doses (Nakahara et al, 1994;Pierno et al, 1995Pierno et al, , 1999.…”
mentioning
confidence: 99%
“…The disruption by statins of lipid rafts in cell membranes has recently been described in association with impaired lymphocyte function. 14 The exposure of human 43 and mouse or rat 24 muscle to therapeutic doses of simvastatin in vitro has been shown to cause a large calcium release from intracellular stores into the cytoplasm in myofibers with weak Ca ϩ2 efflux through the permeability pore. This impairment of calcium homeostasis leads to mitochondrial membrane depolarization, contributing to myotoxicity through altered mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…This needs to be taken seriously. However, others have found that the IC 50 of procaine for Na + current block is 60 mM in peripheral nerve, 57 mM in rat dorsal root ganglion neurons, and so on (34,35). Their concentrations are both a little higher than I HERG block, but lower than the clinically applied dose.…”
Section: Clinical Significancementioning
confidence: 99%